Manajemen Bimbingan dan Konseling SMAN 2 Sangatta Utara - Tri Velyna (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
The purpose of this research is to describe and analyze the guidance and counseling management applied to SMAN 2 North Sangatta, this research uses a qualitative approach. Collecting data using interview techniques, observation and documentation. Data analysis used in this study is an interactive analysis model from Miles and Huberman through data collection, data reduction, data presentation, and drawing conclusions. The informants in the study were school principals, counseling teachers, subject teachers and students. The results showed that guidance and counseling management at SMA 2 North Sangatta consisting of planning, organizing, implementing, and supervising had been carried out quite well but there were several obstacles. (1) Planning, the BK program is based on an analysis of student needs, is flexible, but not yet based on environmental analysis (2) BK is organized, the division of tasks is in accordance with the mechanism but is constrained by time constraints, and still does not have a special schedule for meetings between BK teachers and the elements involved. involved in the organizational structure due to insufficient time, (3) Implementation, the counseling program uses a 17 plus pattern, but some services have not been carried out optimally because the ratio of counseling teachers and students has not been balanced, namely 1:150 students, so program implementation still prioritizes things that are incidental, (4) BK supervision both from internal and external has been carried out but there is no schedule related to the evaluation is still based on needs.